A desulfurization wastewater anticorrosion and wear-resistant material and coating process for slag bin of slag scooping machine
By using nickel, chromium, manganese, and molybdenum metal powder on the surface of the residue slag warehouse, the anti -corrosion -resistant material prepared by metal powder such as metal powder such as nickel, manganese, and molybdenum is used to form a dense protective layer with arc spraying technology to solve the durability of equipment in high corrosion and thermal corrosion environment. The problem has significantly extended the life of the equipment and reduced maintenance costs.
Patent Information
- Application Number
- CN202410276851.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-03-12
AI Technical Summary
The slag silo of the slag retrieval machine faces high corrosiveness, thermal corrosion and wear of suspended particles when dealing with desulfurization wastewater, resulting in a shortening of the equipment service life and an increase in maintenance costs.
The specific hybrid ratio of metal powder such as nickel, chromium, manganese, and molybdenum, and anti -corrosion wear -resistant materials prepared by fine production processes can form a dense protective layer on the surface of the residue scum warehouse through the arc spraying technology.
It significantly improves the corrosion resistance and wear resistance of the equipment, extended the service life of the equipment, reduced the maintenance cost, and maintained stability and durability in the extreme environment.
Smart Images

Figure BDA0004736128160000131 
Figure BDA0004736128160000141 
Figure BDA0004736128160000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal spraying anti-corrosion, in particular to a desulfurization wastewater anti-corrosion and wear-resistant material and coating process for a slag bin of a slag scooping machine. Background Art
[0002] As the core equipment of the wet slag removal system, the slag bin of the slag remover is key to the treatment and cooling of the desulfurized slag. The desulfurized wastewater carried by these slags contains high concentrations of chemical oxygen demand, calcium, magnesium, chloride ions, sulfate ions and other ions, especially chloride ions with a concentration of up to 67,000 ppm, and a pH value usually between 4.0 and 6.5, showing strong corrosiveness. In addition, the desulfurized wastewater has a high content of suspended solids, high hardness, and a solid content of generally 1%-3%, which poses a severe challenge to corrosion prevention.
[0003] In traditional processes, the corrosion resistance measures of the slag bin of the slag extractor often rely on simple anti-corrosion coatings or the use of corrosion-resistant materials, but these measures are difficult to meet the needs of long-term resistance to high temperature and highly corrosive environments. Especially when treating desulfurization wastewater, the corrosion problems involved are more complicated, including not only chemical corrosion, but also thermal corrosion caused by temperature changes, and physical wear of the equipment surface by suspended particles. The combined effect of these factors greatly shortens the service life of the slag bin of the slag extractor and increases maintenance costs.
[0004] Therefore, developing a new material and new process that can effectively improve the corrosion resistance and wear resistance of the slag bin of the slag dredger has become a technical problem that urgently needs to be solved. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a desulfurization wastewater anti-corrosion and wear-resistant material and coating process for a slag bin of a slag scooper.
[0006] Specifically, the technical solution of the present invention is:
[0007] The present invention provides a method for preparing a desulfurization wastewater anticorrosive and wear-resistant material for a slag bin of a slag scooping machine, which specifically comprises the following steps:
[0008] S1: mixing nickel, chromium, manganese and molybdenum in a mixer to obtain core powder;
[0009] S2: filling the core powder into an alloy strip, and drawing the strip to obtain the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover.
[0010] Preferably, the mass percentage content of each metal in the core powder in step S1 is: nickel 25-50%, molybdenum 2-12%, manganese 1-9%, and the balance is chromium.
[0011] Preferably, the mass percentage content of each metal in the core powder is: nickel 30-45%, molybdenum 3-9%, manganese 2-6%, and the balance is chromium.
[0012] Preferably, in step S2, the alloy strip is a Ni-Cr alloy strip.
[0013] Preferably, in the Ni-Cr alloy strip, the Ni content is 10-90wt%, and the Cr content is 10-90wt%.
[0014] Preferably, in the Ni-Cr alloy strip, the Ni content is 70-90wt%, and the Cr content is 10-30wt%.
[0015] Preferably, the filling rate of the core powder in the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover is 25-35wt%.
[0016] The present invention also provides a desulfurization wastewater anti-corrosion and wear-resistant material for a slag bin of a slag scooping machine, which is prepared by the above method.
[0017] The present invention also provides a corrosion-resistant and wear-resistant coating process for a slag bin of a slag dredger, comprising the following steps:
[0018] Y1: Sandblasting of the slag bin surface of the slag scoop machine:
[0019] Y11 surface cleaning: remove surface pollutants inside the slag bin of the slag remover;
[0020] Y12 surface roughness: control surface roughness Rz = 60-80μm;
[0021] Y2: Spraying anti-corrosion coating on the surface of the slag bin of the slag scoop machine: arc spraying is performed on the surface of the slag bin of the slag scoop machine, and the spraying material is the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag scoop machine.
[0022] Preferably, the surface roughening in step Y12 is as follows: quartz sand with a particle size of 2.0-4.0 mm is selected as the sandblasting material, the compressed air working pressure for sandblasting is 0.55-0.8 Mpa, and the exhaust flow rate is 5-6 m 3 / min.
[0023] Preferably, the operation method in step Y12 is as follows: the sandblasting distance is 150-200 mm, the sandblasting angle is 60-90° to the substrate; and the surface roughness Rz is controlled to be 60-80 μm.
[0024] Preferably, the spraying process parameters in step Y2 are:
[0025] Arc voltage: 32-34V;
[0026] Arc current: 160-200A;
[0027] Atomizing air pressure: 0.5-0.6MPa;
[0028] Spraying distance: 150-200mm;
[0029] Metal coating thickness: 0.6-0.8mm.
[0030] The present invention relates to a desulfurization wastewater anti-corrosion and wear-resistant material and coating process for the slag bin of a slag scoop machine. By selecting a specific mixing ratio of metal powders such as nickel, molybdenum, manganese and chromium and a sophisticated production process, the corrosion resistance and wear resistance of the material are effectively improved. The material is applied to the surface of the slag bin of the slag scoop machine using arc spraying technology, and the anti-corrosion and wear-resistant coating formed greatly enhances the ability to resist extreme corrosive environments, thereby significantly extending the service life of the equipment. DETAILED DESCRIPTION
[0031] A method for preparing a desulfurization wastewater anti-corrosion and wear-resistant material for a slag bin of a slag scooping machine, specifically comprising the following steps:
[0032] S1: Mix nickel, chromium, manganese and molybdenum in a mixer to obtain a core powder; the mass percentage content of each metal in the core powder is: nickel 30-45%, molybdenum 3-9%, manganese 2-6%, and the balance is chromium;
[0033] S2: Tie a Ni-Cr alloy strip into a U shape, and then fill the core powder into the U-shaped Ni-Cr alloy strip; then close the Ni-Cr alloy strip to cover the core powder, control the filling rate of the core powder to be 25-35%, and then feed it into a wire drawing die to make it pass through drawing and reducing in diameters of 3.0 mm, 2.6 mm, 2.4 mm, 2.2 mm, and 2.0 mm in sequence to obtain the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover with a diameter of 2.0 mm.
[0034] The main components of the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag scoop machine are nickel, chromium, manganese, and molybdenum, which are made into 2mm diameter wires through wire drawing process, and can be used for large-area supersonic arc spraying. Among them, Ni, Cr, Mn, Mo, etc. have good ductility and acid and alkali resistance, and serve as carriers of hard points. The hard points are embedded in the carrier and evenly distributed. Acid and alkali resistance requirements, the prepared coating works in high-temperature furnace gas containing nitric acid, and has good ammonia resistance, acid resistance, and alkali resistance.
[0035] The present invention uses a carefully designed desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover, and utilizes the unique properties of the four elements of nickel Ni, chromium Cr, manganese Mn and molybdenum Mo, thereby significantly improving the corrosion resistance of the material. The following is a detailed explanation of the principle of improving the corrosion resistance of this material from the perspective of materials science and chemistry:
[0036] Nickel is an excellent corrosion-resistant material that can form a stable passivation film in a variety of corrosive environments to prevent further corrosion. Under high temperature conditions, nickel can maintain good mechanical strength and toughness, improving the corrosion resistance of the material. The addition of nickel helps to improve the overall chemical resistance of the material, especially the resistance to sulfates and chlorides in desulfurization wastewater.
[0037] Chromium is a key element in the manufacture of stainless steel and other corrosion-resistant alloys. It can form a dense chromium oxide passivation film on the surface of the alloy. This film is very stable and can effectively isolate the material from the contact with the corrosive medium, thereby greatly enhancing the corrosion resistance of the material.
[0038] Manganese mainly plays the role of deoxidation and sulfide in the alloy, which can improve the corrosion resistance and processing performance of the material.
[0039] Molybdenum can improve the alloy's resistance to pitting and crevice corrosion. The addition of molybdenum helps to enhance the alloy's tolerance to highly corrosive chemicals in desulfurization wastewater and improves the long-term stability of the material.
[0040] The combination of these four elements optimizes the chemical composition of the material, forming an alloy with high corrosion resistance. Through arc spraying technology, this powder core powder can be evenly distributed on the surface of the substrate to form a uniform and dense protective layer.
[0041] It is unexpectedly found that the present invention can further improve the performance by adding tungsten and / or tantalum to the four elements of nickel Ni, chromium Cr, manganese Mn and molybdenum Mo, especially improving the corrosion resistance in acidic environment (such as sulfuric acid / SO2).
[0042] Preferably, the mass percentage content of each metal in the powder core powder is: nickel 30-45%, molybdenum 3-9%, manganese 2-6%, tungsten and / or tantalum 0.2-0.8%, and the balance is chromium.
[0043] The addition of tungsten to the alloy, especially in high temperature environment, can improve the high temperature strength and corrosion resistance of the material. Tungsten can promote the formation of a more stable passivation layer and enhance the material's resistance to corrosive media such as sulfides and oxides.
[0044] Tantalum is a very stable metal with excellent corrosion resistance. In a corrosive environment, tantalum can form a very stable tantalum oxide film on its surface, which can effectively isolate the metal from the corrosive medium and prevent the corrosion reaction. Even in extreme temperature and chemical environments, this oxide layer can maintain its integrity and protective effect. Therefore, even a very small amount of tantalum can significantly improve the overall corrosion resistance of the alloy.
[0045] A corrosion-resistant and wear-resistant coating process for a slag bin of a slag dredger comprises the following steps:
[0046] Y1: Sandblasting of the slag bin surface of the slag scoop machine:
[0047] Y11 Surface cleaning: remove various pollutants on the inner surface of the slag bin of the slag remover, especially grease, dirt, scale, rust, and corrosion products, and the cleanliness of the working surface reaches Sa3 level;
[0048] Y12 Surface roughness: The combination of thermal spray coating and substrate (the inner surface of the slag bin of the slag scooping machine) is mainly mechanical, which requires that the substrate pretreatment should not only remove oil and rust, but also roughen the substrate so that the substrate has a certain roughness. The surface roughness reaches Rz = 60-80μm as specified in GB / T11373-2017 "Pretreatment of the surface of thermal sprayed metal parts";
[0049] The purpose of sandblasting is to increase the contact area between the sprayed layer and the substrate, improve the bonding degree of the coating, increase the mutual embedding and bite between the coating material and the substrate surface, play the role of "anchor hook", and improve the adhesion between the coating and the substrate.
[0050] Activated surface: Sandblasting provides active surface capabilities for spraying: such as lattice defects, plastic deformation, and a certain stress state, which is beneficial to increase the adhesion between the spray particles and the substrate surface and improve the micrometallurgical bonding ability between the spray particles and the substrate.
[0051] Sandblasting causes a certain amount of residual compressive stress to form on the surface of the workpiece after repeated impact by sand particles. Although the stress value is extremely small, it is beneficial to improve the bonding strength of the coating for the loose workpiece during the spraying process by reducing the thermal stress of the coating. It can also improve the fatigue strength of the workpiece.
[0052] Sandblasting can remove organic pollutants and oxide layers on the surface of the workpiece, increase the plastic deformation of the metal surface grains and cause lattice defects, put the substrate surface in a state prone to chemical reactions, and help to strengthen the physical and chemical bonding between the sprayed particles and the substrate surface.
[0053] Explanation of the damage caused by sandblasting to the tower wall thickness: Sandblasting only removes dirt on the surface, and the thickness of the tower wall removed by blasting is ≤15μm, which is the thinnest thickness and will not affect the thickness of the entire tower wall. Secondly, the sandblasting operation will not cause tearing and blowing damage to the tower wall. Thirdly, the sandblasting operation is carried out evenly, and the thickness reduction of the entire surface is consistent. In summary, sandblasting is only the most effective way to dry, clean, and activate the surface of the tower wall and improve the bonding strength of the coating, and it will not damage the thickness of the tower wall.
[0054] Therefore, it is extremely necessary to perform sandblasting on the workpiece before spraying. And the workpiece after sandblasting should be sprayed as soon as possible. The shorter the time, the better the surface activation effect and the higher the coating quality.
[0055] Specific operation sequence and inspection requirements: First spray quartz sand twice to completely remove rust, oxide scale, coke, etc. on the surface of the steel and reveal a gray-white metallic luster. The role of spraying quartz sand is only to roughen the surface of the substrate to achieve the surface roughness required for spraying without causing any damage to the thickness of the tower wall. Use a roughness sample block for control inspection. After sandblasting, the tower wall surface should be dry, free of dust, oil, oxide scale, rust and other debris, and the surface of the substrate should present a homogeneous gray-white metallic appearance.
[0056] The sandblasting abrasive material should be quartz sand with a particle size of 2.0-4.0mm, with a moisture content of less than 1%, impurities and fine powder content of less than 5%, and sharp edges. The sandblasting abrasive material must be kept clean and dry;
[0057] The compressed air for sandblasting must be clean, dry, oil-free and water-free; the working pressure is 0.55-0.8Mpa, and the exhaust flow rate is 5-6m 3 / min;
[0058] Operation method: Sandblasting distance 150-200 mm, sandblasting angle 60-90° to substrate;
[0059] When multiple people are blasting at the same time in the same space, the distance between them should be no less than 5 meters;
[0060] The arc flame flow of the spray gun is adjusted to a stable state with uniform scattering and no arc break;
[0061] The spray gun sprays vertically to the substrate and reciprocates along the axis of the tower wall at a uniform speed, with a moving speed of 0.3-0.5m / s;
[0062] Reciprocating spraying 9-10 times completes a spraying cycle;
[0063] Use a thermometer to monitor the substrate temperature to ensure it does not exceed 100°C;
[0064] After the coating is accepted, sealing treatment shall be carried out according to the process requirements.
[0065] After the sandblasting operation is completed, the sand and dust on the surface of the workpiece should be blown away layer by layer from top to bottom, and the sand and dust on the sprayed surface should be cleaned up.
[0066] Y2: Spraying anti-corrosion coating
[0067] During the spraying process, the tower wall surface temperature should be controlled at 110-150℃. The thickness of the spray layer should be completed in multiple times. The surface of the spray layer should be flat. Thickness measurement and other items should be carried out after each construction unit is completed. For the spray layer that does not meet the requirements, it should be repaired or re-sprayed immediately.
[0068] The spraying material is a wire material, i.e., the desulfurization wastewater anticorrosive and wear-resistant material for the slag bin of the slag remover prepared by the present invention. During the spraying process, the tower wall base material does not undergo any material changes, does not generate stress, and the tower wall does not deform. The coating is tightly combined with the tower wall base material, does not layer or fall off at high temperatures, has good heat conduction, a smooth surface, and is dust-free. After spraying, the tower wall has good resistance to wear, high-speed erosion, and extreme cold and heat. The service life is more than 1 year. The temperature of the spray layer can reach 800°C-950°C, the coating does not oxidize, is resistant to high-temperature corrosion, does not delaminate, and the material does not change.
[0069] When spraying, follow the principle of "spray up and down, move right, and complete in pieces", that is, spray from top to bottom at a certain speed, and then from bottom to top, move one position to the right each time. When it moves to the right about 1m, return to spray, and do this 8-12 times to avoid uneven spraying or overheating and ensure the quality of the coating.
[0070] The arc spraying system consists of power supply, wire feeder, supersonic arc spray gun (YB500 supersonic arc sprayer), air compressor, gas tank, oil-water separator and other equipment. This spraying technology uses an arc burning at the end of the wire to melt the wire that is evenly fed in. The supersonic airflow accelerated by the Laval nozzle atomizes the melted wire into fine and evenly distributed particles, which are sprayed to the workpiece to form a coating. The particle speed reaches 450-550m / s, and the bonding strength between the coating and the substrate is also significantly improved. The molten particles are mainly combined with the substrate by mechanical, physical and metallurgical methods. Compared with ordinary arc spraying and flame spraying, supersonic arc spraying has higher particle flight speed, stronger bonding strength, lower porosity, high coating uniformity, good density, and the temperature of the sprayed particles is less than 80°C when they reach the surface of the workpiece, so the workpiece will not deform, and a high-quality coating can be obtained.
[0071] Spraying process parameters:
[0072] Arc voltage: 32-34V;
[0073] Arc current: 160-200A;
[0074] Atomizing air pressure: 0.5-0.6MPa;
[0075] Spraying distance: 150-200mm;
[0076] Metal coating thickness: 0.6-0.8mm;
[0077] The spraying method adopts a tic-tac-toe spraying method, with layered and zoned operations. After the local area is sprayed to reach the process design thickness, it will be moved to other areas to ensure the uniform thickness and bonding strength of the spray layer and prevent leakage.
[0078] After spraying, the coating quality should be inspected and the thickness δ2 should be measured. If δ2-δ1 is not less than 0.5mm, it is qualified and can enter the next process. Otherwise, the unqualified parts should be sprayed again. When spraying the wear-resistant layer: the tic-tac-toe spraying method is also used, and the layered and zoned operations are carried out. After the local area spraying reaches the process design thickness, it will be moved to other areas to ensure the uniform thickness and bonding strength of the spray layer and prevent leakage.
[0079] Operation precautions: Work in blocks, spray the local area until it reaches the designed thickness before moving to other areas, and set identification marks at the overlapping parts. During operation, the interlayer temperature shall not be higher than 100℃.
[0080] The wire feeding reel and wire feeding situation are monitored by a dedicated person to ensure smooth wire feeding and prevent the wire from "knotting". At the same time, absolute insulation between the two wires must be ensured to avoid short circuits.
[0081] Before spraying, test spraying should be performed on the test board to adjust the voltage, current, wire feeding speed, compressed air flow, and check the flexible joints and hose joints of the gas circuit for leaks. If special sites such as unstable wire feeding, unstable arc burning, and severe leaks are found, they should be checked and adjusted in time. When adjusting the voltage, the main circuit should be disconnected to avoid damaging the main spray power supply.
[0082] The burnt conductive nozzle during the spraying process should be replaced in time, and the conductive nozzle with excessive processing accuracy is prohibited to be used. If the wire feeding is unstable, the fuse is blown, and the arc is intermittent during the spraying process, the use of the conductive nozzle should be checked first, and the installation of the wire guide tube should be checked again. If it is loose, it should be tightened in time.
[0083] The present invention is carefully designed and implemented through advanced arc spraying technology, and successfully forms a layer of powder core coating composed of nickel, chromium, manganese and molybdenum in an optimized ratio on the surface of the slag bin of the slag remover. This technology ensures the uniform distribution of the powder core on the surface of the substrate, creating a high-performance protective layer that is both corrosion-resistant and wear-resistant. Through the synergistic effect of chemical and physical dual mechanisms, the coating of the present invention provides a solid protective barrier for the slag bin of the slag remover in terms of chemical properties, effectively isolates the corrosive medium, and prevents the invasion of corrosive elements. In terms of physical properties, by improving the uniformity, density and adhesion of the coating, the coating's resistance to mechanical wear is greatly enhanced, and its stability and durability are maintained in extreme corrosive environments.
[0084] In addition, the refined preparation method adopted by the present invention enables the coating to have higher bonding strength and excellent anti-corrosion performance, thereby providing long-term protection for the slag bin of the slag remover and effectively resisting the corrosion of highly corrosive chemicals such as sulfates and chlorides in the desulfurization wastewater. The superior performance of this protective layer not only significantly extends the service life of the equipment in harsh environments, but also significantly reduces the overall operation and maintenance costs by reducing the frequency of shutdown maintenance.
[0085] Embodiment 1:
[0086] A method for preparing a desulfurization wastewater anti-corrosion and wear-resistant material for a slag bin of a slag scooping machine, specifically comprising the following steps:
[0087] S1: mixing the metals in a mixer to obtain a core powder; the mass percentage of the metals in the core powder is: 38% nickel, 6% molybdenum, 4% manganese, and the balance is chromium;
[0088] S2: Tie a Ni80-Cr20 alloy strip of 12mm×0.3mm into a U shape, and then fill the core powder into the U-shaped Ni80-Cr20 alloy strip; then close the Ni80-Cr20 alloy strip to cover the core powder, control the core powder filling rate at 30%, and then feed it into a wire drawing die, and draw and reduce the diameters in order of 3.0mm, 2.6mm, 2.4mm, 2.2mm, and 2.0mm, and finally obtain the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover with a diameter of 2.0mm.
[0089] Embodiment 2:
[0090] The difference from Example 1 is that the mass percentage content of each metal in the powder core powder is: nickel 38%, molybdenum 6%, manganese 4%, tungsten 0.5%, and the balance is chromium.
[0091] Embodiment 3:
[0092] The difference from Example 1 is that the mass percentage content of each metal in the powder core powder is: nickel 38%, molybdenum 6%, manganese 4%, tantalum 0.5%, and the balance is chromium.
[0093] Embodiment 4:
[0094] The difference from Example 1 is that the mass percentage content of each metal in the powder core powder is: nickel 38%, molybdenum 6%, manganese 4%, tungsten 0.35%, tantalum 0.15%, and the balance is chromium.
[0095] Comparative Example 1:
[0096] The difference from Example 1 is that the mass percentage content of each metal in the powder core powder is: nickel 38%, molybdenum 6%, and the balance is chromium.
[0097] Comparative Example 2:
[0098] The difference from Example 1 is that the mass percentage content of each metal in the powder core powder is: nickel 38%, manganese 4%, and the balance is chromium.
[0099] Comparative Example 3:
[0100] The difference from Example 1 is that the mass percentage content of each metal in the powder core powder is: 6% molybdenum, 4% manganese, and the balance is chromium.
[0101] Test Example 1:
[0102] Arc spraying was performed on 17CrNiMo6 clean steel plate (specification: 20×20×5mm). Spraying process parameters: arc voltage: 32V; arc current: 180A; air pressure: 0.6MPa; spraying distance: 180mm; metal coating thickness: 0.7mm.
[0103] (1) Void ratio test
[0104] JB / T7509-94 "Test Method for Void Rate of Thermal Spray Coatings" tests the void rate of coatings and evaluates the density of coatings. The smaller the void rate, the higher the density.
[0105] (2) Corrosion resistance test:
[0106] Weight gain per unit area (mg / cm 2 ) refers to the mass increase per unit area of the sample surface due to corrosion under specific conditions. It is an indicator for evaluating the corrosion resistance of materials. In corrosion or coating experiments, by measuring the mass change of the sample before and after corrosion and dividing it by the surface area of the sample, the value of the weight gain per unit area can be obtained, thereby evaluating the corrosion resistance of the material or the protective effect of the coating. If the value of the weight gain per unit area is small, it means that the material or coating exhibits better corrosion resistance. The specific tests of the present invention are as follows:
[0107] The steel plate obtained after arc spraying was immersed in a corrosion solution 20 times its weight at 80°C for 2 hours and dried at 120°C for 2 hours; the corrosion solution was an aqueous solution of sodium sulfate and sodium chloride, wherein the sodium sulfate content was 8wt% and the sodium chloride content was 12wt%, and the pH was adjusted to 3.5 with dilute sulfuric acid, in order to simulate the environment of desulfurization wastewater under extreme conditions.
[0108] Then, the corrosion was carried out for 96 hours under the conditions of CO2 partial pressure of 1.5MPa, O2 partial pressure of 0.5MPa, SO2 partial pressure of 0.1MPa, temperature of 350℃, and saturated vapor pressure of water vapor. The weight gain per unit area (unit: mg / cm 2 ).
[0109] Void ratio, % <![CDATA[Weight gain per unit area, mg / cm 2 > Example 1 0.74 3.66 Example 2 0.76 3.44 Example 3 0.78 3.20 Example 4 0.73 2.98 Comparative Example 1 0.75 3.79 Comparative Example 2 0.78 4.08 Comparative Example 3 2.49 7.55
[0110] Compared with Example 1, Comparative Example 1 does not contain manganese. The main function of manganese is to improve the processing performance of the alloy and to deoxidize. For the porosity of the coating, its direct effect is relatively small. Manganese indirectly affects the internal structure and purity of the material through deoxidation, which may affect the microstructure of the coating, but the effect on the porosity is relatively limited.
[0111] Compared with Example 1, Comparative Example 2 does not contain molybdenum. Molybdenum in the alloy mainly enhances corrosion resistance, especially resistance to crevice corrosion and pitting corrosion. Although the direct effect of molybdenum is not to control porosity, its absence may lead to a decrease in the corrosion resistance of the alloy, indirectly causing the corrosive medium to more easily corrode the material, thereby increasing the porosity.
[0112] Compared with Example 1, Comparative Example 3 does not contain nickel. The lack of nickel has a greater impact on porosity because nickel plays a key role in forming a strong passivation film and improving the density of the coating. The lack of nickel makes the alloy more susceptible to corrosion in a corrosive environment, and the formation of the passivation layer is hindered, making the coating more susceptible to microscopic defects such as pores.
[0113] Compared with Example 1, Comparative Example 1 does not contain manganese. The deoxidation effect of manganese on the alloy is beneficial to improving the overall purity of the alloy and the uniformity of the microstructure. Deleting manganese may lead to a slight decrease in performance and a slight increase in weight gain per unit area, but the impact is relatively limited because the direct effect of manganese is not the most critical corrosion resistance mechanism.
[0114] Compared to Example 1, Comparative Example 2 does not contain molybdenum. The presence of molybdenum particularly enhances the alloy's resistance to crevice corrosion and pitting corrosion. Removing molybdenum will directly reduce the alloy's protective ability, making the material more susceptible to corrosion by corrosive media, resulting in an increase in weight gain per unit area.
[0115] Compared with Example 1, Comparative Example 3 does not contain nickel. Nickel is a key element for forming a stable passive film and is essential for improving the overall corrosion resistance of the material. The absence of nickel will lead to a significant decrease in the ability of the material to protect against corrosive media, especially in maintaining the stability of the passive film and the ability to resist various chemical corrosion. Therefore, alloys without nickel will show a large weight gain per unit area in a corrosive environment, reflecting poor corrosion resistance.
[0116] By comparing Examples 2-4 with Example 1, we can clearly see that with the addition of tungsten and tantalum, the weight gain per unit area is significantly reduced, indicating an improvement in corrosion resistance.
[0117] In Example 2, the addition of tungsten improves the corrosion resistance of the material, especially the resistance to crevice corrosion and pitting corrosion. The tungstate formed by tungsten in the coating can effectively block the erosion of the corrosive medium and enhance the protective effect of the coating. This enhanced resistance reduces the mass loss of the material surface during the corrosion process, so the weight gain per unit area is reduced.
[0118] In Example 3, tantalum is an extremely stable metal with excellent corrosion resistance. In the coating, tantalum can form a stable oxide film, which has extremely high chemical stability and can effectively isolate the corrosive medium and reduce the corrosion of the coating. The addition of tantalum significantly improves the stability of the coating in acidic and sulfur-containing environments, resulting in a significant reduction in weight gain per unit area.
[0119] In Example 4, the combined use of trace amounts of tungsten and tantalum demonstrates a synergistic effect, which not only improves the corrosion resistance of the coating, but also improves the microstructure of the coating, making the coating more dense and uniform. This synergistic effect further reduces the possibility of contact between the corrosive medium and the coating surface, enhances the overall protective ability of the coating, and thus minimizes the weight gain per unit area. Therefore, preferably, the mass percentage content of each metal in the powder core powder is: nickel 30-45%, molybdenum 3-9%, manganese 2-6%, tungsten 0.1-0.3%, tantalum 0.1-0.5%, and the balance is chromium.
[0120] The stable oxide layer formed by tantalum on the surface of the alloy provides an effective chemical protection for the alloy, isolating the contact with the corrosive medium, and mainly provides protection against chemical corrosion. At the same time, tungsten enhances the alloy's resistance to high-temperature corrosion and wear by improving the material's high-temperature strength and hardness. The protection mechanisms of these two elements complement each other in different corrosion mechanisms and jointly improve the durability of the material. In addition, the combined action of tantalum and tungsten also promotes the formation of a more stable and denser passivation film, improving the alloy's ability to protect itself under conditions of high temperature, high pressure and acidic gas. At the microscopic level, the addition of these elements may refine the grains, enhance the stability of the grain boundaries, and optimize the microstructure of the alloy, thereby improving its overall mechanical properties and corrosion resistance. Improvements in electrochemical properties, such as increased potential and reduced current density, make the alloy more difficult to undergo electrochemical corrosion reactions, especially in acidic environments containing SO2.
[0121] Test Example 2:
[0122] The corrosion resistance test is basically the same as that of Test Example 1, except that the last step does not contain SO2, that is, the corrosion is then carried out for 96 hours under the conditions of CO2 partial pressure of 1.5MPa, O2 partial pressure of 0.5MPa, temperature of 350℃, and saturated vapor pressure of water vapor, and the weight gain per unit area (unit: mg / cm 2 ). The purpose is to simulate an environment without SO2.
[0123] <![CDATA[Weight gain per unit area, mg / cm 2 > Example 1 2.91 Example 2 2.68 Example 3 2.62 Example 4 2.66
[0124] By comparing the data of Test Example 1 (containing SO2 environment) and Test Example 2 (excluding SO2 environment), we can clearly observe the effect of SO2 on the corrosion resistance of the alloy. In the test environment without SO2, each embodiment shows a lower weight gain per unit area than that in the SO2 environment, indicating that it has better corrosion resistance under this condition. Cause analysis shows that SO2 can promote the formation of sulfates in a high temperature and humid environment, and this type of sulfate has a more severe corrosion effect on metals and alloy materials. The presence of SO2 aggravates the corrosiveness of the corrosive environment, increases the corrosion rate of the material, and then leads to an increase in weight gain per unit area. In addition, SO2 may damage the passivation film formed on the surface of the alloy, reducing its stability and protective effect. On the contrary, in the test environment without SO2, since the passivation film is more stable and can more effectively isolate the corrosive medium, a lower weight gain per unit area is recorded in Test Example 2. Therefore, it can be concluded from the comparison between Test Example 1 and Test Example 2 that the presence of SO2 significantly affects the corrosion resistance of the alloy, and in an environment without SO2, the alloy exhibits better corrosion resistance.
[0125] Embodiment 5:
[0126] The anti-corrosion and wear-resistant coating process of the slag bin of the slag dredger includes the following steps:
[0127] Y1: Sandblasting of the slag bin surface of the slag scoop machine:
[0128] Y11 Clean the surface: remove all pollutants on the inner surface of the slag bin of the slag remover, and ensure that the cleanliness of the working surface reaches Sa3 level specified in GBT 8923.1-2011 Surface treatment of steel before coating Visual assessment of surface cleanliness Part 1: Rust grades and treatment grades of uncoated steel surfaces and steel surfaces after complete removal of the original coating;
[0129] Y12 sandblasting treatment: 3.0mm dry quartz sand is used as sandblasting material, the compressed air working pressure for sandblasting is 0.6Mpa, and the exhaust flow rate is 6m 3 / min;
[0130] Operation method: blasting distance 180 mm, blasting angle 80° to substrate;
[0131] Control the surface roughness to reach Rz=70μm as specified in GB / T11373-2017 "Pretreatment of the Surface of Thermal Sprayed Metal Parts";
[0132] Y2: Anti-corrosion coating sprayed on the surface of slag bin of slag dredger:
[0133] Arc spraying is performed on the surface of the slag bin of the slag remover, and the spraying material is a wire material, that is, the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover prepared in Example 1 of the present invention;
[0134] Spraying process parameters:
[0135] Arc voltage: 32V;
[0136] Arc current: 180A;
[0137] Air pressure: 0.6MPa;
[0138] Spraying distance: 180mm;
[0139] Metal coating thickness: 0.7mm.
[0140] Final performance test:
[0141] Coating porosity 0.8%;
[0142] Coating bonding strength: tensile bonding strength ≥45Mpa, shear bonding strength ≥150Mpa;
[0143] The Rockwell hardness of the coating is HRC ≥ 40;
[0144] The bonding strength of the coating is ≥50MPa;
[0145] High temperature oxidation resistance: 6.3mg / cm 2 (750°C oxidation for 250 hours);
[0146] Base temperature ≤80℃ Thermal expansion coefficient 12.5×10 -6 .
[0147] The above construction technology is based on the following national standards:
[0148] GB / T11373-2017 "Pretreatment of the surface of thermally sprayed metal parts"
[0149] GB / T 11375-1999 "Safety of thermal spraying of metals and other inorganic coatings"
[0150] GB8642-2002 "Determination of bonding strength of thermal spray coatings"
[0151] GB8641-88 "Determination of tensile strength of thermal spray coatings"
[0152] GB8640-88 "Method for testing the Rockwell hardness of metal thermal spray coatings"
[0153] JGJ46-2005 "Technical Specifications for Temporary Electricity Safety at Construction Sites"
[0154] GB / T11374-2012 Non-destructive measurement method for thermal spray coating thickness
[0155] JB / T7509-94 "Test method for porosity of thermal spray coatings"
[0156] GB / T 8923.1-2011 Surface preparation of steel before coating Visual assessment of surface cleanliness Part 1: Rust grades and treatment grades of uncoated steel surfaces and steel surfaces after complete removal of existing coatings
[0157] GB5817-86 Classification of Hazard Levels in Industrial Dust Operations
[0158] GB5784-85 "Determination of dust in the air of the workplace"
[0159] GB / T1031-2009 "Product Geometric Technical Specification (GPS) Surface Structure Profile Method Surface Roughness Parameters and Their Values"
[0160] GB / T13288-91 "Evaluation of Surface Roughness Grade of Painted Strong Steel".
[0161] Some of the spraying anti-corrosion projects in which the anti-corrosion and wear-resistant materials prepared by the present invention participate:
[0162]
[0163]
[0164]
[0165] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a desulfurization wastewater anticorrosion and wear-resistant material for a slag bin of a slag dredger, characterized in that: The following steps are involved: S1: mixing nickel, chromium, manganese and molybdenum in a mixer, and then adding tungsten and / or tantalum to obtain core powder; S2: filling the core powder into an alloy strip, and drawing the alloy strip to obtain the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover; The mass percentage content of each metal in the powder core powder is: nickel 30-45%, molybdenum 3-9%, manganese 2-6%, tungsten and / or tantalum 0.2-0.8%, and the balance is chromium.
2. The method for preparing the desulfurization wastewater anticorrosive and wear-resistant material for the slag bin of the slag dredger according to claim 1, characterized in that: In the step S2, the alloy strip is a Ni-Cr alloy strip.
3. The method for preparing the desulfurization wastewater anticorrosive and wear-resistant material for the slag bin of the slag dredger according to claim 2, characterized in that: In the Ni-Cr alloy strip, the Ni content is 70-90wt%, and the Cr content is 10-30wt%.
4. The method for preparing the desulfurization wastewater anticorrosive and wear-resistant material for the slag bin of the slag dredger according to claim 1, characterized in that: The filling rate of the powder core in the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag remover is 25-35wt%.
5. A desulfurization wastewater anticorrosion and wear-resistant material for slag bin of slag scoop machine, characterized in that: The method is prepared by any one of claims 1 to 4.
6. A corrosion-resistant and wear-resistant coating process for a slag bin of a slag dredger, characterized in that: The steps include: Y1: Sandblasting of the slag bin surface of the slag scoop machine: Y11 surface cleaning: remove surface pollutants inside the slag bin of the slag remover; Y12 surface roughness: control surface roughness Rz = 60-80μm; Y2: Spraying anti-corrosion coating on the surface of the slag bin of the slag scoop machine: Arc spraying is performed on the surface of the slag bin of the slag scoop machine, and the spraying material is the desulfurization wastewater anti-corrosion and wear-resistant material for the slag bin of the slag scoop machine as described in claim 5.
7. The anti-corrosion and wear-resistant coating process for the slag bin of the slag dredger according to claim 6, characterized in that: The surface roughness in step Y12 is as follows: quartz sand with a particle size of 2.0-4.0 mm is selected as sandblasting sand material, the compressed air working pressure for sandblasting is 0.55-0.8Mpa, and the exhaust flow rate is 5-6m 3 / min.
8. The anti-corrosion and wear-resistant coating process for the slag bin of the slag dredger according to claim 6, characterized in that: The operation method in step Y12 is as follows: the sandblasting distance is 150-200 mm, the sandblasting angle is 60-90° with respect to the substrate; the surface roughness Rz is controlled to be 60-80 μm; The spraying process parameters in step Y2 are: Arc voltage: 32-34V; Arc current: 160-200A; Atomizing air pressure: 0.5-0.6MPa; Spraying distance: 150-200mm; Metal coating thickness: 0.6-0.8mm.
Citation Information
Patent Citations
Anti-corrosive wear-resistant arc spraying cored wires with nickel base containing Cr3C2
CN101451225A
Wear-resistant iron-based high-speed electric arc spraying cored wire and application thereof
CN116815098A